THE INFLUENCE OF THE PLANTING TIMES OF THE "SHIRIN-PECHAK" AND "ZARGULOBI" MELON VARIETIES ON THE GROWTH AND DEVELOPMENT OF PLANTS - Sadullayev Sanjarbek Madiyarovich; Ochilova Anaxon Atabekovna (Bright Mind Publishing, 2025)
In this scientific article, the results of experiments on the dependence of planting dates of melon varieties on plant development phases, the duration of periods and growth-development in the conditions of Khorezm region: as well as germination, the formation of the first true leaf, pruning, flowers the information about their appearance and their mutual relationship was studied and relevant results were obtained.
Keywords: Melon varieties, phenological phases, planting dates, pruning, male and female flowers, fruiting and ripening.